A high wear-resistant, low-noise tire tread rubber for electric buses and its preparation method and application

By improving the tread glue formula and combining the crosslinking network structure of enhanced resin and hollow glass microbeads, the existing tires' grip reduction and noise-enhancing problems are solved, and the comprehensive performance of high grip, low noise and high wear resistance is achieved, which is suitable for the high-performance tire needs of electric buses.

CN118852750BActive Publication Date: 2025-04-01SHANDONG HUASHENG RUBBER +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410899580.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-05
Publication Date
2025-04-01
Estimated Expiration
2044-07-05

AI Technical Summary

Technical Problem

After the tires of existing new energy electric buses have improved wear resistance, their grip has decreased and their low noise has not been improved, making it difficult to meet the requirements of high grip, low noise and high wear resistance of electric buses.

Method used

Through formulation improvement, a tread glue including natural rubber, polyisoprene rubber, reinforcement resin, hollow glass beads and fillers are prepared. The reinforced resin forms a crosslinking network through the polymerization of cyclohexoxy allyl acetate, monomer A and monomer B, which improves the bonding and compatibility with rubber, enhances the mechanical strength, grip and wear resistance of the tread glue, and reduces noise through the combination of hollow glass microbeads and fillers.

Benefits of technology

The tires are fully equipped with low heat generation, high grip, low noise and high wear resistance, and can still maintain these characteristics during long-term operation, extending the service life of the tire and improving the smooth running of electric buses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004930112460000101
    Figure BDA0004930112460000101
  • Figure BDA0004930112460000111
    Figure BDA0004930112460000111
  • Figure BDA0004930112460000121
    Figure BDA0004930112460000121
Patent Text Reader

Abstract

The present application discloses a high wear-resistant and low-noise tire tread rubber for electric buses and its preparation method and application, which belongs to the technical field of tire preparation for new energy buses. The tread rubber includes by weight: 35-50 parts of natural rubber, 70-80 parts of polyisoprene rubber, 10-15 parts of reinforcing resin, 1-3 parts of hollow glass microspheres, 50-55 parts of fillers, 2-3 parts of vulcanizing agent, 3-10 parts of activator, 2-5 parts of antioxidant, 1-2 parts of accelerator, 1-2 parts of anti-scorch agent; the reinforcing resin is obtained by polymerization of allyl cyclohexyl acetate, monomer A and monomer B, and monomer B is obtained by addition reaction of diacrylate monomer and sulfaguanidine. The tire tread rubber is improved by formula, so that the tire has the characteristics of low heat generation, high grip, low noise and high wear resistance while reducing rolling resistance as much as possible, and the tire prepared by the tread rubber has good durability and can still maintain the above characteristics in long-term operation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a highly wear-resistant, low-noise tire tread rubber for electric buses and a preparation method and application thereof, belonging to the technical field of tire preparation for new energy buses. Background Art

[0002] Electric buses have the advantages of low energy consumption, low noise, high driving stability and zero emissions. According to statistics, as of the end of 2022, China's urban public bus and tram operating lines will have 78,000 lines. Last year, the urban public bus and tram passenger volume reached 35.337 billion, serving nearly 100 million passengers every day. In order to achieve the smooth operation of electric buses, the quality of tires is of paramount importance.

[0003] Since electric buses use electric motors to replace the original engines, the energy supply system produces almost no noise. Since the noise is significantly reduced, the noise of the tires will be more prominent, so it is very necessary to prepare silent tires. Secondly, the current new energy electric buses are heavier, and the torque transmitted by the transmission system is also greater, requiring the tires to have better grip. At the same time, the tires are under greater pressure during emergency stops and sudden braking, so tires with higher strength and wear resistance are required.

[0004] At present, some researchers have also made outstanding contributions to the above requirements. For example, patent CN115895055A discloses a highly wear-resistant new energy electric bus tire tread rubber, which controls the heat generation performance of the rubber by controlling the raw rubber system, vulcanization system and vulcanization conditions of the rubber, and designs the cross-linked network structure density and its bond type distribution to ensure that the tire has low heat generation and low rolling resistance and greatly improves the wear resistance. However, although the wear resistance is greatly improved, the grip of the tire will be reduced, and the low noise of the tire is not improved. Summary of the invention

[0005] In order to solve the above problems, a highly wear-resistant and low-noise tire tread rubber for electric buses and a preparation method and application thereof are provided. The tire tread rubber is improved through the formula so that the tire can reduce the rolling resistance as much as possible while having the characteristics of low heat generation, high grip, low noise and high wear resistance. The tire prepared with the tread rubber has good durability and can still maintain the above characteristics during long-term operation.

[0006] According to one aspect of the present application, a high wear-resistant and low-noise tire tread rubber for an electric bus is provided, which comprises, by weight:

[0007] 35-50 parts of natural rubber, 70-80 parts of polyisoprene rubber, 10-15 parts of reinforcing resin, 1-3 parts of hollow glass microspheres, 50-55 parts of filler, 2-3 parts of vulcanizing agent, 3-10 parts of activator, 2-5 parts of antioxidant, 1-2 parts of accelerator, 1-2 parts of scorch retarder;

[0008] The reinforcing resin is obtained by polymerizing allyl cyclohexyl acetate, monomer A and monomer B, wherein the structural formula of monomer A is shown in formula (1):

[0009] Where n is selected from any integer between 1 and 3;

[0010] Monomer B is obtained by an addition reaction between a diacrylate monomer and sulfonamide.

[0011] The reinforcing resin added in the present application contains double bonds and some amino groups, so the reinforcing resin can form a cross-linked network by itself during the vulcanization process, which interpenetrates with the cross-linked network formed by the rubber, and can bond with the rubber to integrate into the cross-linked network of the rubber, thereby enhancing the bonding with the rubber.

[0012] The construction of the above two cross-linked networks can, firstly, increase the compatibility with the rubber substrate and improve the mechanical strength, grip and wear resistance of the tread rubber; secondly, in combination with hollow glass beads and fillers, they can reflect and absorb vibration energy, so that they have sound insulation and vibration reduction functions in a wider frequency range, thereby significantly reducing the noise generated during tire operation; thirdly, due to the synergy of the chain segment length and various groups in the enhanced resin, the hysteresis loss of the rubber can be reduced, and the heat generation and rolling resistance of the tire can be reduced.

[0013] Optionally, the weight ratio of allyl cyclohexyl acetate, monomer A and monomer B is (1-2):1:(0.5-0.8).

[0014] In the above-mentioned reinforced resin, the presence of monomer A can increase the chain length of the reinforced resin and improve the toughness of the above-mentioned cross-linked network. Allyl cyclohexyl acetate can introduce epoxy side chains. It has been verified by experiments that the introduction of the epoxy side chains can improve the compatibility with hollow glass microspheres and fillers, so that the hollow glass microspheres and fillers can be evenly dispersed in the rubber system, thereby enhancing the mechanical properties and grip of the tread rubber. The monomer B obtained by the reaction of sulfaguanidine and diacrylate monomers has multiple double bonds and a small amount of amino groups, which can adjust the cross-linking point density and the chain length between the cross-linking points of the reinforced resin cross-linking network and the rubber cross-linking network, thereby effectively reducing the deformation and hysteresis loss of the tire and reducing heat generation. In addition, since sulfaguanidine contains benzene rings and sulfur-oxygen double bonds, the presence of benzene rings can enhance the strength of the cross-linking network and improve the wear resistance of the tread rubber. The presence of sulfur-oxygen double bonds can improve the affinity between the system and the vulcanizer, improve the processing performance and vulcanization uniformity of the tread rubber, thereby improving the performance consistency of the tread rubber.

[0015] The presence of the above-mentioned monomer A and diacrylate monomers makes the molecular chain of the reinforced resin contain more ester groups and ether groups, which can significantly improve the temperature resistance of the tread rubber, thereby broadening the use temperature range of the tread rubber. Even in the severe cold weather in winter and the high temperature in summer, it can still maintain high wear resistance, low heat generation, low noise and low rolling resistance, and can also play a role in damping and shock absorption, thereby improving the stability of the operation of electric buses.

[0016] Optionally, the monomer A is selected from 1,3-propylene glycol diacetate (CAS No.: 24493-53-6), 3-(3-prop-2-enoyloxypropoxy)prop-2-enoic acid propyl ester (CAS No.: 1026700-18-4), trimer (1,3-propylene glycol) diacrylate (CAS No.: 68901-05-3)

[0017] Optionally, the weight ratio of the diacrylate monomer to sulfamethoxazole is (3-4):1.

[0018] The above weight ratio can improve the reaction efficiency of the double bonds of the diacrylate monomer and the amino groups in sulfonamide, thereby increasing the double bond content of monomer B. However, due to the steric effect of the amino groups in sulfonamide that reacted first, there are still some unreacted amino groups in monomer B. The presence of these amino groups does not affect the improvement of the overall performance of the tire. However, if the amount of diacrylate monomer added is too small, the number of amino groups in monomer B will increase, which will reduce the number of cross-linking points of the reinforced resin cross-linking network and the binding with the rubber cross-linking network, thereby reducing the overall performance of the tire.

[0019] Optionally, the diacrylate monomer is selected from at least one of 1,6-hexanediol diacrylate, dipropylene glycol diacrylate and tripropylene glycol diacrylate.

[0020] Optionally, the reaction conditions of the diacrylate monomer and sulfonamide are as follows: placing the diacrylate monomer and sulfonamide in a first solvent, adding a catalyst, and reacting at 40-70° C. for at least 4 hours to obtain.

[0021] Optionally, the catalyst is a lithium salt, and the lithium salt is selected from at least one of lithium iodide, lithium bromide, lithium chloride and lithium fluoride.

[0022] Optionally, the amount of the lithium salt added is 2-4% by weight of the sulfaguanidine.

[0023] Optionally, the first solvent is selected from at least one of a mixed solvent of isopropanol and water, a mixed solvent of diethylene glycol butyl ether and water, and a mixed solvent of toluene and water, and in the above mixed solvents, water accounts for 50-60wt%.

[0024] Optionally, the polymerization step of the reinforcing resin is:

[0025] S1: dissolving the allyl cyclohexyl acetate and monomer A in a second solvent, and polymerizing under the action of an initiator to obtain a solution containing an intermediate;

[0026] S2: adding monomer B to the solution containing the intermediate to polymerize, and obtaining the reinforced resin after separation.

[0027] Optionally, the second solvent is selected from at least one of chloroform, ethyl acetate and tetrahydrofuran.

[0028] Optionally, the reaction temperature of step S1 is 80-90° C., and the reaction time is 5-6 h.

[0029] Optionally, the reaction temperature of step S2 is 80-90° C., and the reaction time is 3-5 h.

[0030] Optionally, the filler is selected from at least one of carbon black, nano-silicon dioxide and expanded perlite.

[0031] Optionally, the filler is selected from carbon black, nano silicon dioxide and expanded perlite in a weight ratio of 4:4:1, and the particle size of the expanded perlite is 80-100 μm.

[0032] Preferably, the expanded perlite is modified expanded perlite, and the specific preparation steps are as follows:

[0033] Add activated silica gel to a 0.1-0.2 mol / L sulfaguanidine solution and stir evenly to obtain a modified liquid, wherein the weight ratio of the activated silica gel to the sulfaguanidine solution is 1:(10-15). Place expanded perlite in the modified liquid, wherein the weight ratio of the expanded perlite to the modified liquid is 1:(20-30). Stir at room temperature for 30 minutes, dry at low temperature, and then calcine at 200-250°C for 4 hours. After cooling, grind to a particle size of 80-100 μm.

[0034] The expanded perlite is modified by a modifying liquid containing sulfaguanidine solution and activated silica gel, so that the surface of the expanded perlite is coated with the activated silica gel containing sulfaguanidine. The sulfaguanidine can participate in the cross-linking reaction of the rubber or reinforcing resin, so that the expanded perlite can be evenly dispersed in the cross-linking network, thereby improving the mechanical and thermal properties of the tread rubber, avoiding the migration of the expanded perlite due to long-term use, and improving the stability of the tread rubber. The activated silica gel can form larger pores, thereby adjusting the average pore size of the modified expanded perlite, so that the noise of the tread rubber is further reduced and the shock absorption performance is also improved.

[0035] Preferably, the preparation method of the activated silica gel is: calcining the silica gel at 300-350° C. for 4 hours, and then soaking the silica gel in a mixed solution of ethanol and water at room temperature for at least 6 hours.

[0036] According to another aspect of the present application, there is provided a method for preparing the high wear-resistant and low noise tire tread rubber for electric buses as described in any one of the above items, comprising the following steps:

[0037] (1) mixing the natural rubber, polyisoprene rubber, reinforcing resin and 50% of filler in one step, then adding the remaining 50% of filler, activator, antioxidant and scorch retarder for two-step mixing and then discharging to obtain a mixed rubber;

[0038] (2) adding a vulcanizing agent and an accelerator to the mixed rubber and performing three-step mixing, and then cooling the mixed rubber to obtain the mixed rubber.

[0039] Optionally, the one-step mixing temperature is 60-80° C. and the time is 5-10 min;

[0040] The temperature of the two-step mixing is 80-90°C and the time is 5-10min;

[0041] The temperature of the three-step mixing is 50-70° C. and the time is 2-3 minutes.

[0042] According to another aspect of the present application, there is provided a use of the high wear-resistant, low-noise tire tread rubber for electric buses as described in any one of the above items in the preparation of electric bus tires.

[0043] The beneficial effects of this application include but are not limited to:

[0044] 1. The tire tread rubber of the present application uses natural rubber and polyisoprene rubber as the base material, and the addition of reinforcing resin can form two interpenetrating cross-linked networks to improve the mechanical strength, wear resistance and grip of the tire.

[0045] 2. In the tire tread rubber of the present application, the ratio of cyclohexyl acetate allyl ester, monomer A and monomer B in the reinforcing resin can adjust the number of crosslinking points of the two crosslinking networks and the length of the chain segments between the crosslinking points, thereby reducing the heat generation and rolling resistance of the tire.

[0046] 3. The tire tread rubber of the present application, the addition of the reinforcing resin can improve the compatibility of the hollow glass microspheres and the filler, and can reflect and absorb vibration energy, thereby improving the shock absorption performance of the tire and reducing noise.

[0047] 4. The temperature resistance and weather resistance of the tire tread rubber of the present application are improved, and it can maintain its high performance in both extremely cold weather and high temperature weather, can withstand greater pressure, improve the stability of the operation of the electric bus, and extend the service life of the tire. DETAILED DESCRIPTION

[0048] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0049] Unless otherwise specified, the raw materials in the examples and comparative examples of the present application were purchased through commercial channels.

[0050] Unless otherwise specified, the methods used in the examples and comparative examples of the present application are conventional methods in the prior art.

[0051] The vulcanizing agent used in the following examples is sulfur, the activator is zinc oxide, the antioxidant is antioxidant RD, the accelerator is zinc dibutyl dithiocarbamate, the anti-scorch agent is anti-scorch agent CTP, the particle size of the hollow glass microspheres is 50 μm, and the carbon black is carbon black N330.

[0052] Example 1

[0053] The present embodiment relates to a high wear-resistant and low-noise tire tread rubber for electric buses and a preparation method thereof, the tread rubber comprising: 35 parts of natural rubber, 70 parts of polyisoprene rubber, 10 parts of reinforcing resin, 1 part of hollow glass microspheres, 50 parts of fillers, 2 parts of vulcanizers, 3 parts of activators, 2 parts of antioxidants, 1 part of accelerators, and 1 part of scorch retarder, wherein the filler is selected from carbon black and expanded perlite in a weight ratio of 4:1, and the particle size of the expanded perlite is 80 μm;

[0054] The preparation steps of the reinforced resin are:

[0055] S0: 1,6-hexanediol diacrylate and sulfaguanidine in a weight ratio of 3:1 are placed in a mixed solvent of isopropanol and water (the proportion of water is 50wt%), lithium iodide catalyst is added, and the amount of the catalyst added is 2% of the weight of sulfaguanidine, and the reaction is carried out at 70°C for 4h, and then filtered, washed, and dried to obtain monomer B;

[0056] S1: dissolving allyl cyclohexyloxyacetate and trimer (1,3-propylene glycol) diacrylate in a weight ratio of 2:1 in a mixed solvent of chloroform and tetrahydrofuran (the weight ratio of chloroform and tetrahydrofuran is 1:1), adding 2% azobisisobutyronitrile based on the weight of trimer (1,3-propylene glycol) diacrylate, and polymerizing at 80° C. for 5 h to obtain a solution containing an intermediate;

[0057] S2: Adding monomer B to the solution containing the intermediate, the weight ratio of trimer (1,3-propylene glycol) diacrylate to monomer B is 1:0.8, polymerizing at 90°C for 3h, and obtaining a reinforced resin after rotary evaporation, washing, and column chromatography separation.

[0058] The preparation method of tire tread rubber comprises the following steps:

[0059] (1) mixing natural rubber, polyisoprene rubber, reinforcing resin and 50% of filler at 60° C. for 10 min in one step, adding the remaining 50% of filler, activator, antioxidant and anti-scorch agent, mixing in two steps at 80° C. for 10 min, and then draining to obtain a mixed rubber;

[0060] (2) Add vulcanizing agent and accelerator to the mixed rubber and mix them in three steps at 50°C for 3 minutes. After the rubber is discharged and cooled, tread rubber 1# is obtained.

[0061] Example 2

[0062] The present embodiment relates to a high wear-resistant and low-noise tire tread rubber for electric buses and a preparation method thereof, the tread rubber comprising: 50 parts of natural rubber, 80 parts of polyisoprene rubber, 15 parts of reinforcing resin, 3 parts of hollow glass microspheres, 55 parts of fillers, 3 parts of vulcanizing agents, 10 parts of activators, 5 parts of antioxidants, 2 parts of accelerators, and 2 parts of scorch retardants, wherein the filler is selected from nano-silicon dioxide and expanded perlite in a weight ratio of 4:1, and the particle size of the expanded perlite is 100 μm;

[0063] The preparation steps of the reinforced resin are:

[0064] S0: dipropylene glycol diacrylate and sulfaguanidine in a weight ratio of 4:1 are placed in a mixed solvent of diethylene glycol butyl ether and water (the proportion of water is 60wt%), lithium bromide catalyst is added, and the amount of the catalyst added is 4% of the weight of sulfaguanidine, and the reaction is carried out at 40°C for 6h, and then filtered, washed, and dried to obtain monomer B;

[0065] S1: dissolving allyl cyclohexyl acetate and 1,3-propylene glycol diacetate in a weight ratio of 1:1 in a mixed solvent of chloroform and tetrahydrofuran (the weight ratio of chloroform and tetrahydrofuran is 1:1), adding 2% azobisisobutyronitrile based on the weight of 1,3-propylene glycol diacetate, and polymerizing at 90° C. for 5 h to obtain a solution containing an intermediate;

[0066] S2: adding monomer B to the solution containing the intermediate, the weight ratio of 1,3-propylene glycol diacetate to monomer B is 1:0.5, polymerizing at 80°C for 5h, and obtaining a reinforced resin after rotary evaporation, washing, and column chromatography separation.

[0067] The preparation method of tire tread rubber comprises the following steps:

[0068] (1) mixing natural rubber, polyisoprene rubber, reinforcing resin and 50% of filler at 80° C. for 5 min in one step, adding the remaining 50% of filler, activator, antioxidant and anti-scorch agent, mixing in two steps at 90° C. for 5 min, and then draining to obtain a mixed rubber;

[0069] (2) Add vulcanizing agent and accelerator to the mixed rubber and mix them in three steps at 70°C for 2 minutes. After the rubber is discharged and cooled, tread rubber 2# is obtained.

[0070] Example 3

[0071] The difference between this embodiment and embodiment 1 is that in the preparation step S0 of the reinforced resin, tripropylene glycol diacrylate and sulfamethoxazole in a weight ratio of 3:1 are placed in a mixed solvent of toluene and water (water accounts for 50wt%) to react, and the rest is the same as in embodiment 1 to obtain tread rubber 3#.

[0072] Example 4

[0073] The difference between this embodiment and embodiment 1 is that the filler is selected from carbon black, nano silicon dioxide and expanded perlite in a weight ratio of 4:4:1, and the rest is the same as embodiment 1, to obtain tread rubber 4#.

[0074] Example 5

[0075] The difference between this embodiment and embodiment 1 is that the expanded perlite is modified expanded perlite, and the specific preparation steps are as follows:

[0076] Silica gel was calcined at 300°C for 4 hours, then placed in a mixed solution of ethanol and water and soaked at room temperature for 6 hours to obtain activated silica gel, activated silica gel was added to a 0.1 mol / L sulfaguanidine solution and stirred evenly to obtain a modified solution, the weight ratio of activated silica gel to sulfaguanidine solution was 1:15, expanded perlite was placed in the modified solution, the weight ratio of expanded perlite to the modified solution was 1:30, stirred at room temperature for 30 minutes, low-temperature dried and calcined at 200°C for 4 hours, and ground to a particle size of 80 μm after cooling. The rest was the same as in Example 1 to obtain tread rubber 5#.

[0077] Example 6

[0078] The difference between this embodiment and embodiment 1 is that the expanded perlite is modified expanded perlite, and the specific preparation steps are as follows:

[0079] Silica gel was calcined at 350℃ for 4h, then immersed in a mixed solution of ethanol and water at room temperature for 6h to obtain activated silica gel, activated silica gel was added to a 0.2mol / L sulfaguanidine solution and stirred evenly to obtain a modified solution, the weight ratio of activated silica gel to sulfaguanidine solution was 1:10, expanded perlite was placed in the modified solution, the weight ratio of expanded perlite to the modified solution was 1:20, stirred at room temperature for 30min, dried at low temperature, calcined at 250℃ for 4h, and ground to a particle size of 80μm after cooling. The rest was the same as in Example 1 to obtain tread rubber 6#.

[0080] Example 7

[0081] The difference between this embodiment and embodiment 1 is that the weight ratio of allyl cyclohexyl acetate to trimer (1,3-propylene glycol) diacrylate is 0.5:1, and the rest is the same as embodiment 1, to obtain tread rubber 7#.

[0082] Example 8

[0083] The difference between this embodiment and embodiment 1 is that the weight ratio of trimer (1,3-propylene glycol) diacrylate to monomer B is 1:1, and the rest is the same as embodiment 1, to obtain tread rubber 8#.

[0084] Example 9

[0085] The difference between this embodiment and embodiment 1 is that the weight ratio of 1,6-hexanediol diacrylate to sulfaguanidine is 2:1, and the rest is the same as embodiment 1, to obtain tread rubber 9#.

[0086] Comparative Example 1

[0087] The difference between this comparative example and Example 1 is that the reinforcing resin is obtained by polymerization of allyl cyclohexyl acetate and monomer A, and the preparation steps are as follows: dissolving allyl cyclohexyl acetate and trimer (1,3-propylene glycol) diacrylate in a weight ratio of 2:1 in a mixed solvent of chloroform and tetrahydrofuran (the weight ratio of chloroform and tetrahydrofuran is 1:1), adding 2% azobisisobutyronitrile by weight of monomer A, polymerizing at 80°C for 5h, and obtaining the reinforcing resin after rotary evaporation, washing, and column chromatography separation. The rest is the same as Example 1, and the comparative tread rubber D1# is obtained.

[0088] Comparative Example 2

[0089] The difference between this comparative example and Example 1 is that the reinforcing resin is obtained by polymerizing trimer (1,3-propylene glycol) diacrylate and monomer B, and the preparation of the monomer B is the same as that of Example 1. The preparation steps of the reinforcing resin are as follows: dissolving trimer (1,3-propylene glycol) diacrylate and monomer B in a weight ratio of 1:0.8 in a mixed solvent of chloroform and tetrahydrofuran (the weight ratio of chloroform and tetrahydrofuran is 1:1), adding 2% azobisisobutyronitrile accounting for the weight of trimer (1,3-propylene glycol) diacrylate, polymerizing at 90°C for 3h, and obtaining the reinforcing resin after rotary evaporation, washing, and separation by column chromatography. The rest is the same as that of Example 1, and a comparative tread rubber D2# is obtained.

[0090] Comparative Example 3

[0091] The difference between this comparative example and Example 1 is that the added amount of the reinforcing resin is 20 parts, and the rest is the same as Example 1, to obtain a comparative tread rubber D3#.

[0092] Test Example 1

[0093] The tread rubbers prepared in the above embodiments and comparative examples were subjected to the following experimental tests, and the test results are shown in Table 1:

[0094] 1. Mechanical properties test: tensile strength and elongation at break were tested in accordance with GB / T 528-2009.

[0095] 2. Wear resistance test: Wear resistance test is carried out in accordance with GB / T1689-1998 Determination of wear resistance of vulcanized rubber. The lower the Akron wear value, the better the wear resistance of the tread rubber.

[0096] 3. Hot air aging tensile aging coefficient: tested in accordance with GB / T 3512-2014 standard. The larger the hot air aging tensile aging coefficient, the better its resistance to heat and oxygen aging.

[0097] 4. Compression heat generation: A rubber dynamic compression heat generation instrument is used to test the compression heat generation of the above tread rubber.

[0098] Table 1

[0099]

[0100] Test Example 2

[0101] According to the same manufacturing process of bus tires, the finished tires obtained in the above embodiments and comparative examples were processed to prepare tires, and the following tests were performed on the tires. The results are shown in Table 2.

[0102] 1. Noise reduction performance: The noise reduction test is carried out in accordance with GB / T32789 1016 "Tire Noise Test Method - Drum Method". After the test, the tires are drummed for 48 hours under the same conditions, left to stand for 12 hours, and then the noise test is carried out again. The lower the noise value, the better the tread rubber performance.

[0103] 2. Wet skid resistance: Install each test tire on an all-wheel drive vehicle and test the braking distance from the braking start position on a wet cement road at a first speed of 50km / h. The smaller the braking distance value, the better the anti-wet skid resistance and grip of the tread rubber.

[0104] 3. Rolling resistance coefficient: Tire rolling resistance is the energy loss per unit driving distance. The tire rolling resistance coefficient is the ratio of the rolling resistance expressed in Newtons to the tire load expressed in Newtons. The smaller the rolling resistance coefficient, the smaller the tire rolling resistance.

[0105] Table 2

[0106]

[0107]

[0108] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.

Claims

1. A high wear-resistant and low noise tire tread rubber for electric buses, characterized in that: By weight, it includes: 35-50 parts of natural rubber, 70-80 parts of polyisoprene rubber, 10-15 parts of reinforcing resin, 1-3 parts of hollow glass microspheres, 50-55 parts of filler, 2-3 parts of vulcanizing agent, 3-10 parts of activator, 2-5 parts of antioxidant, 1-2 parts of accelerator, 1-2 parts of scorch retarder; The reinforcing resin is obtained by polymerizing allyl cyclohexyl acetate, monomer A and monomer B, wherein the structural formula of monomer A is shown in formula (1): Where n is selected from any integer between 1 and 3; Monomer B is obtained by addition reaction of diacrylate monomer and sulfonamide; The weight ratio of allyl cyclohexyl acetate, monomer A and monomer B is (1-2):1:(0.5-0.8); The weight ratio of the diacrylate monomer to sulfonamide is (3-4):

1.

2. The high wear-resistant and low noise tire tread rubber for electric buses according to claim 1, characterized in that: The diacrylate monomer is selected from at least one of 1,6-hexanediol diacrylate, dipropylene glycol diacrylate and tripropylene glycol diacrylate.

3. The high wear-resistant and low noise tire tread rubber for electric buses according to claim 1, characterized in that: The reaction conditions of the diacrylate monomer and sulfonamide are as follows: placing the diacrylate monomer and sulfonamide in a first solvent, adding a catalyst, and reacting at 40-70° C. for at least 4 hours to obtain the product.

4. The high wear-resistant and low noise tire tread rubber for electric buses according to claim 1, characterized in that: The polymerization steps of the reinforced resin are: S1: dissolving the allyl cyclohexyl acetate and monomer A in a second solvent, and polymerizing under the action of an initiator to obtain a solution containing an intermediate; S2: adding monomer B to the solution containing the intermediate to polymerize, and obtaining the reinforced resin after separation.

5. The high wear-resistant and low noise tire tread rubber for electric buses according to claim 4, characterized in that: The reaction temperature of step S1 is 80-90°C, and the reaction time is 5-6h.

6. The high wear-resistant and low noise tire tread rubber for electric buses according to claim 4, characterized in that: The reaction temperature of step S2 is 80-90° C., and the reaction time is 3-5 h.

7. The method for preparing a high wear-resistant and low noise tire tread rubber for electric buses according to any one of claims 1 to 6, characterized in that: The steps include: (1) mixing the natural rubber, polyisoprene rubber, reinforcing resin and 50% of filler in one step, then adding the remaining 50% of filler, activator, antioxidant and scorch retarder for two-step mixing and then discharging to obtain a mixed rubber; (2) adding a vulcanizing agent and an accelerator to the mixed rubber and performing three-step mixing, and then cooling the mixed rubber to obtain the mixed rubber.

8. Use of the high wear-resistant and low noise tire tread rubber for electric buses according to any one of claims 1 to 6 in the preparation of electric bus tires.

Citation Information

Patent Citations

  • Low-heat-generation high-wear-resistance tear-resistant engineering tire tread rubber and preparation method thereof

    CN115160659A

  • High-wear-resistance new energy electric bus tire tread rubber, preparation method, application and tire

    CN115895055A